Determination of number of Extracranial and Intracranial Atherosclerotic Arterial Stenosis in Patients of Ischemic Stroke with Diabetes Mellitus under DSA Evaluation (Bangladesh Journal of Neuroscience, 2013)
Objective: To evaluate the solitary & multiple site of extracranial and intracranial atherosclerotic arterial stenosis in patients of ischemic stroke with diabetes mellitus.Methodology: This retrospective observational study was conducted among the patients having ischemic stroke with diabetes mellitus who were admitted in Dhaka Medical College & Hospital (DMCH) out patient department during March 2010 to February 2011. A total of 30 patients with ischemic stroke and diabetes mellitus were included in the study. CT scan of brain was done to every patient to confirm the diagnosis. Digital subtraction angiography was performed for complete evaluation.Result: The mean (±SD) age was 57.9±9.2 years with a range from 43 to 80 years and male female ratio was 29:1. Among 21 patients with extracranial stenosis, either single, double and triple or more lesions were found in 53.3%, 85.7% and 87.5% of patients respectively. Again among 9 patients with intracranial stenosis, it was observed that 46.7% of patients had single lesion stenosis, 14.3% of patient had double lesion stenosis and 12.5% of patients had triple or more lesion stenosis. Double (85.7%) and triple (87.5%) lesions were significantly (p70% stenosis in extracranial arteries and 21.1% in intracranial arteries. Patients with >70% stenosis were significantly (p